Polygenic Basis and Variable Genetic Architectures Contribute to the Complex Nature of Body Weight —A Genome-Wide Study in Four Chinese Indigenous Chicken Breeds - Yuan, Yangyang; Peng, Dezhi; Gu, Xiaorong; Gong, Yanzhang; Sheng, Zheya; Hu, Xiaoxiang (Frontiers in Genetics, 2018)
Body weight is one of the most important economic traits for animal production and breeding, and it has been studied extensively for its phenotype-genotype associations. While mapping studies have mostly aimed at finding as many loci as possible that contributed to the variation in body weight, the role of other factors in its genetic architecture, including their frequencies in the population and their interactions, have been largely overlooked. To comprehensively characterized the genetic architecture of body weight, we performed a Genome-wide association study (GWAS) both at the single-marker and haplotype level on birds from four indigenous Chinese chicken breeds (Chahua, Silkie, Langshan, Beard), rather than studying crosses between two founder lines. Additionally, samples from two more breeds (Red Junglefowl and Recessive White) were included to better reflect variable genetic characteristics across populations. Six loci were mapped in this study, revealing the polygenic basis underlying body weight. Moreover, by further examining the frequencies of the significantly associated haplotypes in each subpopulation and their effect sizes, most of the loci were found to affect body weight in the Beard chicken breed alone. Two loci in GGA9 and GGA27, however, had a common effect on body weight across subpopulations, showing that different underlying genetic mechanisms contribute to the phenotypic variability. These findings, particularly the variable genetic architectures found in different loci, improve our understanding of the overall genetic contributions to the large variability in body weight among Chinese indigenous chicken breeds. Thus they will have important implications for future chicken breeding.